In vivo assay of Gigantochloa apus shoot extract as biolarvicide for myiasis-causing fly larvae - Sadana, Aqsa Aufa Syauqi; Istiadi, Hermawan; Halleyantoro, Ryan; Muniroh, Muflihatul (Published by Universitas Gadjah Mada, 2025)
The use of synthetic insecticides in treating myiasis is associated with adverse side effects and potential disruption of metabolic systems, prompting interest in natural alternatives. This study investigated the in vivo larvicidal efficacy of Gigantochloa apus bamboo shoot extract, formulated as a spray gel. Twenty-five Wistar rats were randomly divided into 5 groups: a negative control group, a positive control (ivermectin), and 3 treatment groups receiving of 1%, 3%, and 5% G. apus bamboo shoot extract. Myiasis was induced by introducing fly larvae into standardized wounds. Treatments were applied topically twice daily for 32 hr, and larval mortality was assessed every 8 hr. Phytochemical screening and GC-MS analysis revealed the presence of bioactive compounds, including alkaloids, flavonoids, tannins, saponins, and hydrogen cyanide, all of which are known for their larvicidal, neurotoxic, and antiproliferative properties. The 5% extract group showed the highest mortality rate (100%) at 32 hr. The LC50 and LC95 values were determined at 1.43% and 6.01%, respectively. Compared to the standard ivermectin treatment, the 5% extract demonstrated a shorter lethal time and more rapid larval death. Morphological examination revealed darker abdominal segments in the dead larvae, indicating a potential interaction with the digestive tract. These findings indicate that G. apus bamboo shoot extract has potential larvicidal activity and can be an effective natural alternative for treating myiasis.